Comparison of IVC Diameter and Pro-BNP for Judgeouos use of IV Fluids in Critical ill Patients on IPPV - Muhammad Sohaib Ishaq, Syed Mazhar Ali Naqvi, Akhtar Ali, Muhammad Imran Sharif, Masood Alam (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the diameter of IVC and levels of Pro-BNP for use of IV fluids in critical ill patients on IPPV Study Design: Descriptive cross sectional study Place and duration of study: At the department of Critical Care Medicine the Services hospital, Lahore from April 2021 to March 2022 Methodology: The study was conducted after the approval of hospital ethical committee and from each patient written consent form was also obtained we enrolled 77 patients in our study after fulfilling of inclusion criteria. The base line and echocardiographic characteristics were analyzed including NT–proBNP and inferior vena cava diameter. IVC diameter was determined with the help of echocardiography. NT–proBNP was determined with the help of ELISA kit. For statistical analysis we used SPSS 23 version. Pearson correlation test was also used to check the relation between NT–proBNP and inferior vena cava diameter. Correlation was significant at p < 0.05. Results: The mean age of patients was 62.06 ± 7.54. 37 (48.1 %) were male and 40 (51.9 %) were female. The results of brain natriuretic peptide (pg/mL) was 280. 58 ± 40.82 and NT–proBNP (pg/mL) was 1981.25 ± 278.88. The Inferior Vena Cava size was 1.86 ± 0.77 cm. The results of correlation was significant (p < 0.01) in between the inferior vena cava size and NT–proBNP. The value of correlation was 0.753. Conclusion: Natriuretic peptides are linked to IVC size in patients with congestive heart failure. These findings imply that left-sided echocardiography and the biomarker assessment have a complimentary purpose. IVC diameter can be beneficial in assessing volume status and discriminating between congestion and non-congestion heart failure. Keywords: IVC diameter, levels of Pro-BNP, IV fluids, IPPV